Последний десантник - Зверев Сергей Иванович (Спецназ ВДВ, 2011)
Экземпляры: ф-5 (ретроконверсия) / Инвентарный номер: 46774 / Цена: 136.00 / Сис.шифр: Р2 / Авт.знак: З-43 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6